Effect of classical music on reducing blood pressure in children - Saloma Klementina Saing; Oke Rina; Rafita Ramayati; Rusdidjas Rusdidjas (Paediatrica Indonesiana, 2008)
Background High blood pressure remains a public healthproblem. High blood pressure in children and adolescent is amajor risk for cardiovascular disease in adulthood which cancause high morbidity and mortality. Listening to the classicalmusic can be used as an alternative in reducing high bloodpressure.Objective To investigate the effect of classical music in reducingblood pressure in children with high normal blood pressure andor hypertension.Methods Eighty eight students of Sidorame Senior High SchoolMedan with blood pressure 2: 120/80 mmHg or blood pressure2: 90 percentile Task Force were included in this study. TheVivaldi's Four Seasons was played for 30 minutes using Sony stereocassette recorder and earphone. The students' blood pressure weremeasured after listening to the music.Results The reduction of students' blood pressure in the classicalmusic group was greater than control group (L'ISBP, L'IDBP9.4lmmHg, 6.05mmHg versus 4.37mmHg, 2.23mmHg) andshowed statistically difference.Conclusion Listening to the classical music can reduce bloodpressure in children with high blood pressure.